2005
DOI: 10.2486/indhealth.43.24
|View full text |Cite
|
Sign up to set email alerts
|

The Nighttime Nap Strategies for Improving Night Shift Work in Workplace

Abstract: Nighttime napping is an effective measure to prevent adverse effects due to night shift work. A characteristic of nighttime nap is that it can result in considerably deeper sleep. Several studies have shown that taking nighttime naps suppressed increasing sleepiness, decreasing alertness during the period following awaking from a nap, and prevented disturbance of circadian rhythm ("anchor sleep"). The length of daytime sleep after night shift, when combined with a nighttime nap, is shorter than that without na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 32 publications
0
33
1
1
Order By: Relevance
“…Importantly, these night shift tests were conducted in circadian rhythm and recovery controlled pre-selected shift arrangements, where sleepiness was pronounced in the HJS-group only. During night shift, especially the high-strain nurses might benefit from planned naps, which suppress sleepiness 47,48) . However, job strain was not associated with other PVT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these night shift tests were conducted in circadian rhythm and recovery controlled pre-selected shift arrangements, where sleepiness was pronounced in the HJS-group only. During night shift, especially the high-strain nurses might benefit from planned naps, which suppress sleepiness 47,48) . However, job strain was not associated with other PVT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Shift workers are compelled to work and sleep at irregular hours not consistent with their innate circadian rhythms, and thereby suffer from severe sleepiness and fatigue compared with day workers 12,13) . Some researchers in Japan have investigated the effects of nocturnal napping during duty as a nightshift countermeasure for the problem of sleepiness and fatigue in nightshift workers [14][15][16][17][18][19][20][21][22][23][24][25][26] . According to these studies, nocturnal napping could reduce sleepiness and fatigue, and help maintain circadian rhythms, and thereby have beneficial effects for work safety, workers' sleep health and quality of life 26) .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Restorative napping, defined as a purposeful, brief sleep period, has been identified as a potential strategy to improve performance, reduce fatigue, and increase vigilance for individuals working extended hours or during night shift. [13][14][15][16][17] In order for restorative napping to occur, it has been suggested that managers of health care facilities provide a safe and comfortable resting place for nurses working night shift, ensure that nurses do not miss breaks, and use strategies to combat shift work issues such as fatigue. [18][19][20][21][22] Historically, napping by health care staff during night shift has not been condoned by management, with anecdotal evidence to suggest this still may be the case in some jurisdictions.…”
mentioning
confidence: 99%